Unhappiness and Crime : Evidence from South Africa - Powdthavee, Nattavudh
This paper is the first of its kind to study quality of life responses of crime victims. Using cross-sectional data from the OHS97 survey of South Africa, we show that victims report significantly lower well-being than the non-victims, ceteris paribus. The calculated ‘compensating variation’ suggests that it would take, on average, an extra $10,000 per month to offset the psychological costs of crime. Happiness is lower for nonvictimized respondents currently living in higher crime areas. However, we find a strong evidence for females that criminal victimization hurts, but hurts less if the crime rate on our reference group is high.Happiness ; Quality of Life ; Crime ; Stigma ; South Africa